Hematoma Ventricle Distance on Computed Tomography Predicts Poor Outcome in Intracerebral Hemorrhage - Deng, Lan; Zhang, Yun-Dong; Ji, Jian-Wen; Yang, Wen-Song; Wei, Xiao; Shen, Yi-Qing; Li, Rui; Zhang, Shu-Qiang; Lv, Xin-Ni; Li, Xin-Hui; Tang, Zhou-Ping; Wu, Guo-Feng; et al. (Frontiers in Neuroscience, 2020)
Objective: To investigate the relationship between hematoma ventricle distance (HVD) and clinical outcome in patients with intracerebral hemorrhage (ICH). Methods: We prospectively enrolled consecutive patients with ICH in a tertiary academic hospital between July 2011 and April 2018. We retrospectively reviewed images for all patients receiving a computed tomography (CT) within 6 hours after onset of symptoms and at least one follow-up CT scan within 36 hours. The minimum distance of hematoma border to nearest ventricle was measured as HVD. Youden index was used to evaluate the cutoff of HVD predicting functional outcome. Logistic regression model was used to assess the HVD data and clinical poor outcome (modified Rankin Scale 4-6) at 90 days. Results: A total of 325 patients were included in our final analysis. The median HVD was 2.4 mm (interquartile range, 0-5.7mm) and 119 (36.6%) patients had poor functional outcome at 3months. After adjusting for age, admission Glasgow coma scale, intraventricular hemorrhage, baseline ICH volume, admission systolic blood pressure, hypertension, HVD≤2.5mm was associated with increased odds of clinical poor outcome (odds ratio, 3.59, [95%CI=1.72-7.50]; P =0.001) in multivariable logistic regression analysis. Conclusion: HVD allows physicians to quickly select and stratify patients in clinical trials, thereby sever as a novel and useful addition to predict ICH prognosis.